SLEEP HYGIENE OF STUDENTS - Niyazova O. A.; Yuldasheva F. U.; Norqulov S. J. (Innovate Conferences, 2025)
The factors that determine people's health are based on their lifestyle, which is determined by the mode of work and rest. The primary role in it is played by sleep, which is the main and absolutely irreplaceable type of rest, contributing to the restoration of strength and energy resources of the body. To replenish your energy consumption on a daily basis, you need a healthy sleep, during which the main recovery processes of tissues and organs take place, active processing of information for the past day takes place, the work of internal organs is adjusted, and a significant amount of hormones is secreted that ensure the constancy of the internal environment. Regular sleep and wake disorders can lead to memory disorders, psycho-emotional disorders, and decreased performance. Violation of the biological rhythms of the body, the regime and duration of sleep leads to deterioration of the physical and psycho-emotional state, depression, behavioral disorders and aggressiveness, to deterioration of memory, thinking, concentration and attention span, reduces the speed of psychomotor reactions, which negatively affects the results of studies. It is believed that more than a quarter of the population to some extent suffer from various sleep disorders, which is associated with the modern rhythm of life.